1991
DOI: 10.1002/aic.690370402
|View full text |Cite
|
Sign up to set email alerts
|

Methods of deterministic chaos applied to the flow of thin wavy films

Abstract: The structure of thin, wavy falling films was studied to evaluate whether the random-appearing wave structure is a result of deterministic chaos or a purely stochastic process. The time-varying film thickness was obtained at different spatial locations near the point of wave inception for flow rates in the range of lntroduc t ionThe hydrodynamic behavior of thin wavy falling films has been a subject of intensive investigation for about forty years. These films are widely employed in equipment for heat transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Time signals from natural phenomena are subject to noise which can significantly increase the correlation dimension in nonlinear time-sequence analysis (Lacy et al, 1991). In this study, a low-pass filter set at 20 Hz has been used in data sampling.…”
Section: Correlation Dimensionmentioning
confidence: 99%
“…Time signals from natural phenomena are subject to noise which can significantly increase the correlation dimension in nonlinear time-sequence analysis (Lacy et al, 1991). In this study, a low-pass filter set at 20 Hz has been used in data sampling.…”
Section: Correlation Dimensionmentioning
confidence: 99%
“…Experimental studies of falling films have been done by, among others, Kapitza & Kapitza (1949), Krantz & Goren (1971), Portalski & Clegg (1972), Alekseenko, Nakoryakov & Pokusaev (1985), and Lacy, Sheintuch & Dukler (1991). As summarized by Alekseenko et al, in most of the experiments performed, twodimensional regular waves are observed only near the wave-inception line.…”
Section: Introductionmentioning
confidence: 99%
“…However, even when the symmetric disturbances are expected to have the largest growth rate, the other unstable modes may influence the observed pattern. The last assertion is based on experimental data, 9 where azimuthal waves are often observed. Anyway, the symmetric perturbations are investigated not only to compare their growth with that of the asymmetric modes, but also to understand the effect that Coriolis and centrifugal forces have on all the modes.…”
Section: Introductionmentioning
confidence: 99%